Identificação fenotípica e molecular de Rhodococcus equi e Dietzia maris em bubalinos - Viana, Luciane Ribeiro (2007)
The bacterial identification in laboratories of microbiology is achieved by using several morphophysiological and genetic factors. Some members of the actinomycetes group, like the genera Rhodococcus, Gordonia, Nocardia and Dietzia have similar phenotypical characteristics. As result of this, the laboratorial detection of these microorganisms is often faced with bacterial identification problems. The present work analyzed 24 bacterial isolates from milk and skin of buffalo females (Bubalus bubalis), which previously had been identified as Rhodococcus equi, by using a restricted number of phenotypical tests for bacterial characterization. Using additional biochemical tests and molecular tools, the goal of this study was to perform the characterization of these isolates, as well as the differentiation of other microorganisms closely related. The results of the phenotypical tests had not allowed distinguishing definitely the isolates, once that they demonstrated relationship with two correlated genera, Rhodococcus and Dietzia. Despite the fact, these results allowed the separation of the isolates in three distinct biotypes. Only one of the isolates was confirmed as R. equi through the PCR multiplex specifically for this specie, as well DNA sequencing and DNA fragment analysis. All the other isolates only could be precisely identified after the DNA sequencing, where they were characterized as Dietzia maris. The sensitivity profile to antimicrobials demonstrated the biggest resistance of the D. maris isolates to oxacillin and rifampin, 96% and 87% respectively. The R. equi isolate, presented resistance to amikacin, oxacillin, penicillin, rifampin and tetracycline. Alert for the risk of the incorrect identification of the bacterial isolates by using diagnostic analysis based on phenotypical tests in order to differentiate R. equi and D. maris, besides the necessity to use of complementary tests for differentiation of these microorganisms.